New Teacher Associations: Comparative Analysis of Teachers’ Political Participation in Chile and Spain - Ortiz-Mallegas, Sebastián; Carrasco-Aguilar, Claudia; Luzón Trujillo, Antonio; Torres-Sánchez, María Mónica (SAGE, 2025)
Teacher associations have historically been important agents of teacher advocacy. However, they are now facing challenges due to the crisis of traditional structures. This has allowed the emergence of new teacher associations that seek other forms of participation in educational governance. Via a comparative qualitative analysis of education between Chile and Spain, this study examined the repercussions of associationism in two forms of regulating teacher participation in educational governance: regulated and de facto. The results show how in Chile, a new social force has been created to overcome the political ineffectiveness of associations, whereas in Spain, independence from political parties has been sought through the technification of trade unionism. These findings highlight critical differences in the political strategies of teacher associations in both countries, with implications for the future of educational governance. The study also discusses the broader consequences of associationism in the context of labor market shifts and the changing landscape of teaching professionals.
Keywords: Profesores - Asociaciones; Teacher associationism; Political participation; Teacher trade unionism; Comparative education; Struggle